PERAN KEBIJAKAN PUBLIK DALAM MENGOPTIMALKAN SINERGI PENTAHELIX GUNA MEWUJUDUKAN PENDIDIKAN BERKUALITAS (SDGs 4) DI SURABAYA - Dicky Andhika Pradana; Maherza Cahya Diastara; Firre An Suprapto; Indah Prabawati (STKIP Pesisir Selatan, 2026)
This study aims to examine the role of public policy in optimizing Pentahelix collaboration to achieve quality education in line with Sustainable Development Goals (SDGs) 4 at the Dinas Pendidikan Kota Surabaya. The main issue addressed is the suboptimal collaboration among stakeholders in education policy, which leads to disparities in learning quality and the effectiveness of educational program implementation. This research employs a qualitative approach with a descriptive-analytical design, utilizing secondary data in the form of policy documents, performance reports, SDGs reports, and academic literature related to collaborative and network governance. The findings indicate that public policy in Surabaya has moved toward a collaborative approach involving the five key actors of the Pentahelix model, namely government, academia, business sector, community, and media. However, the implementation of this collaboration has not been fully optimal due to several challenges, including sectoral ego, disparities in resource capacity, lack of policy integration, and weak coordination sustainability. From the perspective of collaborative governance, the main challenges lie in trust, communication, and continuity of the collaborative process. Meanwhile, from a network governance perspective, the partnerships among stakeholders have not yet been strongly and systematically established.